USE OF MODERN INFORMATION TECHNOLOGIES IN THE DEVELOPMENT OF STUDENT’S BIOLOGICAL COMPETENCIES BASED ON A SYNERGISTIC APPROACH - Sharipova Dildora Rajabovna (International Scientific and Current Research Conferences, 2023)
This article, based on a synergetic approach to teaching biology, provides information about the role and significance of the use of information technologies that increase the educational and creative activity of students, increasing the efficiency of the educational process.